Characteristics of convalescent plasma donors and their antibody titers in Bangladesh - Datta, Ponkaj K.; Rahman, M. Mujibur; Kabir, Ahmedul; Hoque, M. Mazharul; Rahman, Motlabur; Hoque, Mohammad Mahfuzul; Islam, Kashfia; Islam, Khairul; Al-Mamun, A. B. M.; Hasan, Pratyay (International Journal of Advances in Medicine, 2021)
Background: Convalescent plasma is considered a promising therapy for severe COVID-19 disease. It is collected from the voluntary donors. Measurement of the antibody titer is necessary before transfusion to predict the outcome in the recipients. Characteristics of the convalescent plasma donors in Bangladesh and their antibody titers are not known. Methods: Convalescent plasma was collected from the voluntary donors who survived the COVID-19 disease to transfuse to the severe COVID-19 patients under a randomized control trial. Total IgG antibody titer was measured in the donor plasma by indirect enzyme-linked immunosorbent assay. Data was collected in a preformed questionnaire before donor plasma collection. Results: The median age is 32 (18-55) years. Fever, cough, sore throat, diarrhea was most common among 68.3% of the symptomatic participants and the remaining 31.7% were asymptomatic at the time when they were RT-PCR positive. Overall, 57.1% of participants had mild symptoms, 11.1% had moderate symptoms and none had severe symptoms. Participants’ antibody titers were measured 41.68±14.072SD days after the RT-PCR positive date. Rapid qualitative test could not detect antibody in 11 (17.5%) potential donors. Of the remaining 52 (82.5%) antibody positive participants titer was measured in 43 participants and found 1:320 in 17 (27.0%) (n=63), 1:160 in another 17 (27.0%) (n=63) and 1:80 in rest of the 9 (14.28%) (n=63) Participants. The mean titer of the donors who were hospitalized during their illness (1:274.29) was statistically significantly higher (p=0.043, CI>95%). The mean titer was also higher in female than in male, symptomatic than asymptomatic participants and in donors of A positive blood group. However, these finding are not statistically significant. Antibody titer does not correlate with time of RT-PCR negativity from initial RT-PCR positivity, time from RT-PCR positivity to titer date, age and body mass index. Conclusions: All RT-PCR positive COVID-19 patients subsequently may not develop antibody. Although antibody titer among hospitalized symptomatic patients was significantly higher, further study is needed to recommend optimal convalescent plasma donor criteria.